Biochemical, histopathological and clinical evaluation of delayed effects caused by methamidophos isoforms and TOCP in hens: Ameliorative effects using control of calcium homeostasis - Emerick, Guilherme Luz [UNESP]; Ehrich, Marion; Jortner, Bernard S.; Oliveira, Regina V.; DeOliveira, Georgino H. [UNESP] (Elsevier B.V., 2012)
This work evaluated the potential of the isoforms of methamidophos to cause organophosphorus-induced delayed neuropathy (OPIDN) in hens. In addition to inhibition of neuropathy target esterase (NTE) and acetylcholinesterase (AChE), calpain activation, spinal cord lesions and clinical signs were assessed. The isoforms (+)-, (+/-)- and (-)-methamidophos were administered at 50 mg/kg orally; tri-ortho-cresyl phosphate (TOCP) was administered (500 mg/kg, po) as positive control for delayed neuropathy. The TOCP hens showed greater than 80% and approximately 20% inhibition of NTE and AChE in hen brain, respectively. Among the isoforms of methamidophos, only the (+)-methamidophos was capable of inhibiting NTE activity (approximately 60%) with statistically significant difference compared to the control group. Calpain activity in brain increased by 40% in TOCP hens compared to the control group when measured 24h after dosing and remained high (18% over control) 21 days after dosing. Hens that received (+)-methamidophos had calpain activity 12% greater than controls. The histopathological findings and clinical signs corroborated the biochemical results that indicated the potential of the (+)-methamidophos to be the isoform responsible for OPIDN induction. Protection against OPIDN was examined using a treatment of 2 doses of nimodipine (1 mg/kg, i.m.) and one dose of calcium gluconate (5 mg/kg, iv.). The treatment decreased the effect of OPIDN-inducing TOCP and (+)-methamidophos on calpain activity, spinal cord lesions and clinical signs. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Chiral organophosphate pesticides; Methamidophos; Acetylcholinesterase; Neuropathy target esterase; Calpain; Treatment of OPIDN